(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Over the past decades, the world has been engulfed by religion in a massive way. Starting with Israel’s victory in the June 1967 Six-Day War, which initiated link between Zionism and Religious Orthodox in Israel, and continuing through the 911 attacks to the rise of ISIS. Religion has therefore been a driving factor in relations among and within states. Scholars like Timothy Shah (2012) pointed that religion has now emerged as one of the most significant and influential factors in global affairs but remains the least examined factors in the professional study and practice of world affairs. Religion is under-theorized in IR because of the dominant notions such as secularism, democracy, nation-state etc. all of which are the product of Western centric knowledge system. This article will provide analysis on waves of theorizing religion and IR by looking at contemporary developments to the rise of ISIS where religion has become a cause for augmented international conflicts.